CFD model to reduce automobile development costs related to refueling system - Stoker, T. McKay, author; Dake, Mangesh, author; Windom, Bret, author; Henderson, Marc, author (Colorado State University. Libraries, 2018)
Testing procedures for automobile refueling systems can be costly. To reduce the amount of testing during the design of refueling systems, car manufacturers desire a CFD tool predictive of system performance. The potential of such a method is demonstrated here.
307 - McKay Stoker
CFD model for an automobile refueling system
Department of Mechanical Engineering, Colorado State University.
Honda R&D Americas, Inc.